On the Construction of Rough Quotient Modules in Finite Approximation Spaces - Adelia, Lisa; Fitriani; Faisol, Ahmad; Anwar, Yunita Septriana (Integra: Journal of Integrated Mathematics and Computer Science, 2025)
Let S be a set and φ an equivalence relation on S. The pair (S, φ) forms an approximation space, where the relation φ partitions S into mutually disjoint equivalence classes. For any subset B' ⊆ S, the lower approximation Apr(B') is defined as the union of all equivalence classes entirely contained in B', while the upper approximation Apr(B') is the union of all equivalence classes that have a non-empty intersection with B'. The subset B' is called a rough set in (S, φ) if Apr(B') ≠ Apr(B'). If, in addition, B' satisfies certain algebraic conditions, it is termed a rough module. This paper investigates the construction of rough quotient rings and rough quotient modules within such approximation spaces. The approach is developed using finite sets to facilitate the algebraic formulation and analysis of these rough structures.